PENGEMBANGAN PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS SAINTIFIK PADA PEMBELAJARAN IPA KELAS VI SDN GANDASARI 1 - Sri Rahayu Kurniasih (Journal of Business Education and Social, 2021)
The purpose of this research is to develop teaching materials in the form of Scientific-based LKPD in science learning and knowing the quality of the material teaching in the form of LKPD produced. This study uses the Borg model and Gall. The population in this study was class VI at SDN Gandasari 1. The sampling technique in this study used a small-scale questionnaire and large scale. Small-scale sampling of 10 people from class VI and dam large-scale sampling of 23 people from class VI. Instruments that used include interviews, questionnaires, and test instruments. Research result this development meets the "feasible" criteria in the expert validation questionnaire assessment language by 80%, the assessment of media experts by 82% with the criteria of "very" feasibleâ€ and the assessment of the education expert questionnaire was 92% with the criteria of â€œveryâ€ worthy". In addition, the practical limited trial met the â€œvery goodâ€ criteria, on a small-scale trial assessment involving 10 students of class VI SDN Gandasari 1 obtained a percentage result of 4.5 and a large-scale trial assessment that involving 23 grade VI students of SDN Gandasari 1, the percentage results obtained 4.7 with the criteria of "very good". From the results of the stages carried out by researchers shows that scientific-based LKPD in science learning is "Very" feasibleâ€, practical and effective for use in science learning media Themes 1 Save Living Creatures Subtheme 1 Plants My Friends.